Determinação do teor de elementos leves em amostras oriundas da indústria de petróleo através da interpretação do perfil Compton - Barbosa Junior, Gilberto José (2017)
The techniques that use X-rays as a form of excitation with the intention of studying the microscopic properties of materials has been widely discussed and improved over the last century. Among these techniques are some well-known ones, as is the case of X-ray diffraction (XRD) and X-ray fluorescence spectroscopy (FRX). The latter has been used primarily for elemental chemical analysis. However, due to the technological evolution of the last decades, several methods of analysis have been incorporated to it. One such method refers to the interpretation of the Compton effect. The analysis of the interaction of X-rays with a material from the point of view of the behavior of the Compton profile has been explored since the 30’ s decade of the last century, however, only in the 70’s decade, due to technological advances such as the synchrotrons, interest in this analysis became more effective. In this work the interpretation of the Compton effect through the excitation of materials with X-rays coming from a traditional XRF equipment (tube of rhodium, power of 2700 W, model S4Pioneer, from Bruker AXS), as an alternative for the determination of the concentration of carbon in samples from the oil industry. Therefore, this work dealt with the analysis of 3 samples of coke and 7 samples of crude petroleum oils in order to validate computational routines previously developed within a package of data processing routines for XRD and XRF (called IIL package), which originated software of interest of the research group like the IILXRF2012, the IILXRR2012 and now the IILCOMPTON. Through the latter, it was possible to the construction of the theoretical Compton profiles for all compositions of interest. The analysis was based on the evaluation of the peak heights ratio (R / C = Rayleigh / Compton) between coherent and incoherent scatterings as a function of concentration. This procedure gave us a way to obtain the quantitative carbon content in the cokes and in the crude oils. Due to the presence of scale (based on the chemical element Ba), the expected linear relationship between the carbon content and the R / C ratio changes in slope and for their explanation a model was suggested here, with three parameters a, b and c, for the behavior of the R / C ratios with the concentrations of CH2 and BaO for the samples of coke.